Syllabus of Vocational High School Based on ESP Approach - Dewi, Sri Utami (Dinamika Ilmu, 2015)
This study is designed as a case study and concerned on qualitative data, which reflected what actually happened in the area of case study. The Principal, the English Teachers and Students placed as the key informants. The data gained from the informants by applying in depth interview, questionnaire, documentation and observation. The data are analyzed by employing two methods, those are: descriptive qualitative and descriptive quantitative. There are two problems in this study that can be seen from two perspectives; syllabus designing and studentsâ needs analysis. From the perspectives of syllabus designing, the problem arise on defining a syllabus typically as the content standart which is commonly and formally provided by the higher authority (i.e. Ministry of National Education). In evidence, the existence of UN (Ujian Nasional/National Examination) makes teachers come into problems. Moreover, from learnersâ needs analysis perspective, teachers define Target Situation Analysis (TSA) mainly as the content of studentsâ subject matters of their majors rather than studentsâ linguistic performance after finishing the course. Furthermore, the teachers define the Present Situation Analysis (PSA) mainly as studentsâ strengths/weaknesses in following the English course.